21 Follicular Unit Transplantation or Follicular Unit Excision: Planning and Decision-Making (Hair Transplantation, 2023)
In modern hair restoration surgery, follicular units can be harvested in one of two ways: strip-follicular unit transplantation (strip-FUT or FUT), which is the microsurgical dissection of follicular units out of a strip of donor material (FUT), and follicular unit excision (FUE), where the follicular units are extracted individually and directly from the donor area. Both FUE and FUT are outstanding techniques and selecting the most appropriate technique for each patient is not always a simple task because many factors need to be taken into consideration. The decision will be based on patients’ goals and expectations, hair characteristic, age, gender donor area, etc. Each technique has its own advantages and disadvantages. FUE used to have high levels of transection and fragile grafts with a risk of poor survival. However, FUE has improved significantly over the last few years. Today, follicular transection, survival, and aesthetic results can be the same for both FUE and FUT. A major advantage of FUE in patients’ eyes is that it does not produce a linear scar and has a less traumatic postoperative course. This has led to high patient demand and rapid growth of the procedure to the point that today, more FUE is performed than FUT. Often, it is not a difference in recipient area aesthetic results as much as a personal preference with respect a donor scar and postoperative course that determines a patient’s choice.For example, a young male may sport a short hairstyle and not want a linear scar (no matter how fine), while a female or middle-aged executive may not want to undergo the extensive donor shaving required for FUE. Although both techniques are acceptable in many cases, there are still some notable instances that FUE or FUT is the preferred technique.
Keywords: follicular unit quality; donor supply; transection rates; complications; hair transplant surgery; hair growth